Reproduction range of garfish, Belone belone (L.), in the northern Baltic Sea - Veneranta, Lari; Urho, Lauri (Memoranda Societatis pro Fauna et Flora Fennica, 2021)
The garfish (Belone belone (L.)) annually migrates from the North Sea to the Baltic Proper. Before this study, the known reproduction areas were located in the southern Baltic Sea up to the Islands of Gotland, Saaremaa and Hiiumaa. However, the larvae collected with a beach seine in 2005 and further observations of 0+ larvae and juveniles after that indicated successful reproduction in the northern Gulf of Finland and the southern Gulf of Bothnia. These catches of 0+ garfish and several other observations of garfish larvae and juveniles during recent decades demonstrate that today the species is annually also reproducing in the northern Baltic Sea. The salinity limit for garfish reproduction is not precisely known; however, the lowest reported value 5-6 ‰ fits well with our observations. We recorded garfish larvae along shallow sandy shores where the temperature is higher than in adjacent open water areas. We suggest that the longterm increase of surface water temperatures in the Baltic Sea have enabled the reported expansion of garfish reproduction range.